2019
DOI: 10.1177/0021998319837339
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the stacking sequence on the low-energy impact resistance of flax/PA11 composite

Abstract: In this paper, the low-energy impact behavior of a fully biobased composite made of bio-sourced polyamide 11 resin reinforced with flax fibers was investigated. Different composite laminates were studied in order to determine the stacking sequence effects on the impact behavior of these composites. Four stacking sequences were manufactured: unidirectional [0°]8, cross-ply [0°/90°]2s, sandwich-like [02°/902°]s and quasi-isotropic [45°/0/−45°/90°]s. A low impact energy of 3.6 J was applied on these laminates by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Since no delamination occurred in the two parts of the material separated by rupture in the fracture morphology of SF-CW and DF-CW, it was concluded that this hybrid structure can still maintain good overall performance after low-speed impact, which demonstrated better performance than traditional materials. 41,42…”
Section: Resultsmentioning
confidence: 99%
“…Since no delamination occurred in the two parts of the material separated by rupture in the fracture morphology of SF-CW and DF-CW, it was concluded that this hybrid structure can still maintain good overall performance after low-speed impact, which demonstrated better performance than traditional materials. 41,42…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Therefore, many researchers have examined the behaviour of flax fibre-reinforced composites under single lowvelocity impacts. [17][18][19][20][21] Ramakrishnan et al 22 have conducted an experimental assessment of the low-velocity impact damage on flax/polypropylene and flax/epoxy laminates constituted, respectively, of 10 and 5 plies with equivalent areal density and thickness. Through optical microscope imaging, these authors have found that the damage mechanisms leading to the failure of these composites are mainly related to fibre breakage, matrix cracking and transverse cracking, with more pronouncing delamination in the flax/epoxy composite.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, polyamide 11 is not biodegradable and has been already validated for durable engineering applications in various sectors such as automotive, biomedical, and sports. In this case, PA11 composites have already been the subject of studies [ 28 , 29 , 30 , 31 , 32 ], but, to the best of our knowledge, no data on the performance of PA11/basalt composites are available so far. That said, taking into account the inevitable technological challenges induced by the use of biomaterials on an industrial scale, and with the aim of further investigating the reinforcement and damage mechanisms triggered in bio-composites, this research work deals with composite systems obtained by combining two commercial PA11 bio-resins and two basalt fiber fabrics with different architecture.…”
Section: Introductionmentioning
confidence: 99%